The word learning profile of adults with developmental language disorder. (January 2020) - McGregor, Karla K; Arbisi-Kelm, Timothy; Eden, Nichole; Oleson, Jacob
Background and aims: Previous investigations of word learning problems among people with developmental language disorder suggest that encoding, not retention, is the primary deficit. We aimed to replicate this finding; test the prediction that word form, not the linking of form to referent, is particularly problematic; and determine whether women with developmental language disorder are better word learners than men with developmental language disorder. Methods: Twenty adults with developmental language disorder and 19 age-, sex-, and education-matched peers with typical language development attempted to learn 15 words by retrieval practice. Their retention was measured one day-, one week-, and one month after training. Results: The participants with developmental language disorder required more exposures to the word-referent pairs than the participants with typical language development to reach mastery. While training to mastery, they made more errors in word form production, alone or in combination with errors in linking forms to the correct referents, but the number of no attempts and pure link errors did not differ by group. Women demonstrated stronger retention of the words than men at all intervals. The developmental language disorder and typical language development groups did not differ at the one-day- and one-month retention intervals but the developmental language disorder group was weaker at the one-week interval. Review via retrieval practice at the one-day and one-week interval enhanced retention at the one-month interval; the review at one week was more beneficial than the review at one day. Women benefitted more from the review opportunities than men but the developmental language disorder and typical language development groups did not differ. Conclusions: Adults with developmental language disorder present with weaknesses in the encoding of new words but retention is a relative strength. Encoding word forms is especially challenging but encoding word-to-referent links is not. We interpret this profile, and the evidence of a female advantage, as consistent with the Procedural Circuit Deficit Hypothesis. Implications: When treating a client with developmental language disorder whose goal is to increase vocabulary knowledge, the interventionist should anticipate the need for multiple exposures to new words within activities that highlight the forms of the words and support their memory and production. Periodic review should serve to support long-term retention.